Influences of Tip Cooling Injection on Tip Clearance Control at Design and Off-Design Incidences - Maosheng Niu; Shusheng Zang (International Journal of Rotating Machinery)
A numerical investigation has been performed to study the influences of cooling injection from the blade tip surface on controlling tip clearance flow in an unshrouded, high-turning axial turbine cascade. Emphasis is put on the analysis of the effectiveness of tip injection when the approaching flow is at design and off-design incidences. A total of three incidence angles are investigated, −7.4°, 0°, 0°, 0°, and 7.6°, 0° relative to the design value. The results indicate that even at the off-design incidences, tip injection can also act as an obstruction to the tip clearance flow and weaken the interaction between the passage flow and the tip clearance flow. It is also found that tip injection causes the tip clearance loss to be less sensitive to the incidences. Moreover, with injection, at all these incidences the heat transfer conditions are improved significantly on the blade tip surface in the middle and aft parts of blade. Thus, tip injection is proved to be an effective method of controlling tip clearance flow, even at off-design conditions. Beside that, an indirect empirical correlation is observed to be able to perform well in predicting the losses induced by tip clearance flow at design and off-design conditions, no matter whether air injection is active or not.